1985
DOI: 10.2337/diacare.8.2.125
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Symptomatic, Diabetic Neuropathy in an Insulin-treated Population

Abstract: The prevalence of symptomatic sensorimotor polyneuropathy has been determined in a population of 382 insulin-treated diabetic subjects aged 15-59 yr. Forty-one subjects (10.7%) were found to have diabetic neuropathy, according to strict diagnostic criteria that required the presence of symptoms and signs of nerve dysfunction in the absence of peripheral vascular disease. There was a significant correlation between glycosylated hemoglobin levels and motor conduction velocity in the median and peroneal nerves in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
1
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(51 citation statements)
references
References 0 publications
4
43
1
1
Order By: Relevance
“…One such study reported that about 20 % of diabetic patients had symptomatic neuropathy; however, about 50 % were found to have objective evidence of diabetic polyneuropathy [17]. Our results confirm the well-established correlations between the prevalence of neuropathy and age [9,[18][19][20], duration of diabetes [9,[18][19][20][21], and metabolic control [9,20,21]. Significant associations have also been reported with height [5,22,23], cigarette smoking [9], the presence of retinopathy [9,21], both background and proliferative, and reduced levels of HDL-cholesterol [9].…”
Section: Discussionsupporting
confidence: 88%
“…One such study reported that about 20 % of diabetic patients had symptomatic neuropathy; however, about 50 % were found to have objective evidence of diabetic polyneuropathy [17]. Our results confirm the well-established correlations between the prevalence of neuropathy and age [9,[18][19][20], duration of diabetes [9,[18][19][20][21], and metabolic control [9,20,21]. Significant associations have also been reported with height [5,22,23], cigarette smoking [9], the presence of retinopathy [9,21], both background and proliferative, and reduced levels of HDL-cholesterol [9].…”
Section: Discussionsupporting
confidence: 88%
“…In the absence of a precise agreed definition of diabetic neuropathy, comparison of the prevalence of the condition between different epidemiological studies is difficult, although most definitions based on clinical features are similar [22]. Our data confirms the association of diabetic polyneuropathy with age and duration of diabetes [23], and highlights a strong relation with glycaemic control independent of diabetes duration.…”
Section: Discussionsupporting
confidence: 76%
“…The diagnostic procedures used in studies of DPN have included assessment of symptoms alone [8] or signs alone [22], quantitative sensory tests [23], and various combinations of these methods: symptoms and signs [6,9,10]; signs and electrophysiological tests [14]; symptoms, signs and electrophysiological test [11,13]; and symptoms, signs, electrophysiological tests and quantitative sensory tests [24,25]. This variety of methods has contributed to discrepancies among the results.…”
Section: Discussionmentioning
confidence: 99%